Aborto provocado e seletivo na interface da saúde e do direito - Wiese, Iria Raquel Borges (2012)
Abortion is considered an ethical problem of public health, and this stands just when there are conflicts between moral rights and obligations. So, actors are perceived in different scenes claiming a decision-making power about the life. They are doctors, lawyers, government officials and others. The reasons to investigate the abortion from these professionals are justified by the fact that these are representatives of biopower from an institutional place, whether in the health care of women in situations of abortion or in formulating the complaint and in the judgment and interpretation of the rights. Objectives: to analyze the beliefs of health-care professionals and jurists about the abortion and selective abortion. Method: the sample was composed of 16 health professionals (doctors, nurses and psychologists), as well as by 10 professionals of law (prosecutors and judges). Initially, a type structured interview was conducted with the participants in order to investigating their beliefs about selective abortion and the abortion. Then, they replied to a questionnaire. Quantitative data were analyzed through descriptive statistics (frequency, average, standard deviation). The interviews were operationalized based in categories, processed in a series of steps. Results: the data of questionnaire pointed out a rigid position of the participants regarding the change in criminal legislation on abortion, which are greatly influenced by their religious beliefs. There was a lack of information from professionals about the documentation required for the authorization of the practice of legal abortion and fetal malformation. For interviews, emerged two thematic classes: abortion and selective abortion. The first covered the categories: attitude, legal aspects, bio psychosocial aspects and coping proposals. The second covered the categories attitude and legal aspects. The beliefs contrary to abortion practice focused on heteronomy and sacredness of life. Favorable beliefs, in turn, emerged only among health professionals, anchored in the perspective of reproductive and sexual rights, reducing risks and damage and, finally, on women's autonomy over their own body. Jurists had a stiffer punishment on the positioning of women who practice abortion. The participants suggested the public politics and education, as sexual education, adoption programs, psychological and social assistance and, for the ones who showed favorable beliefs, its decriminalization in order to reduce risk and damage of unsafe abortion for the confrontation of abortion. In General, some beliefs have referred strictly to the group of jurists, because of the peculiarities of this profession. Others, however, seemed not to relate to the professional group itself, but other aspects which may demarcate groups, following the example of beliefs linked to heteronomy of life and, in contrast, reproductive autonomy. Conclusion: the Brazilian society needs to broaden the discussion of abortion. It s necessary to exit of the extremes "against" and "favour" abortion and see that this topic is of a complexity that cannot be summarized by these words, or terminate the legal or ethical point of view, unlike, cover a wide range of considerations, which might be observed throughout this study.